PpERF1b-like enhances lignin synthesis in pear (Pyrus pyrifolia) ‘hard-end’ fruit - Jin, Xiaoshan; Cheng, Chenxia; Qi, Qi; Zhou, Suping; Wang, Caihong; Zhang, Yong; Sun, Chao; Wang, Yuling; Dang, Ruihong; Yang, Shaolan (Frontiers in Plant Science, 2022)
The hard-end is a disorder of pear fruit, however, the mechanisms underlying its development remain unknown. In this study, we found that the hard-end fruit contained a higher transcript abundance level of ethylene-response factor 1b-like (PpERF1b-like) and released more ethylene compared to normal pear. In the ethephon treated normal fruit, flesh tissues accumulated more lignin together with elevated expression of PpERF1b-like. Overexpressing PpERF1b-like transiently in fruit and stably in callus increased lignin accumulation and the expression of lignin biosynthesis genes; the opposite results were observed in fruit showing repressed expression of PpERF1b-like. These results confirmed the role of PpERF1b-like in promoting hard-end formation through promoting lignin synthesis. This study provided valuable information for further clarifying the regulation of hard-end formation in pear.